Hubungan Keseimbangan Dengan Kemampuan Passing Bawah Dalam Permainan Bolavoli Pada Tim Putri STKIP Kie Raha Kota Ternate - Alief Lam Akhmady; Rusmiyanti Naipon (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the relationship between balance and the ability to pass down in volleyball on the STKIP Kie Raha women's team, Ternate City. This research is a research with correlational design. The subject of this research is the women's team STKIP Kie Raha Ternate City, totaling 21 athletes. Analysis of the data using the Pearson product moment correlation formula at a significant level α = 0.05. The results of the calculation of data analysis of the two variables show that, r count = 0.530 r table = 0.444 at a significant level α = 0.05. So it was concluded that there was a very significant relationship between balance and the ability to pass down in volleyball on the STKIP Kie Raha women's volleyball team, Ternate City.